A Study on the Image of Missionaries to China in the Literature in the 20th Century - WANG, Lijun (Journal of Research for Christianity in China (JRCC), 2025)
Various missionary images have appeared in the literary works of the 20th century. As a group of foreign images, the missionary images in each work have special significance. By systematically combing and analyzing the images of missionaries in the literary works of the 20th century, the author classifies them into three categories: devout and kind-hearted humanitarians, insidious and hypocritical aggressors, and Christians with a combination of Secularity and religion, and concludes that the differences in the image creation of missionaries are related to the writers’ personal experience and their spiritual beliefs, "social collective imagination" and the background of the times.